Genetic Variation of Sorghum (Sorghum bicolor L.) at Several Colchicine Concentrations Based on Agronomic Characteristics - Adam, Marta; Husain, Indriati; Yamin, Mayasari; Nurdin; Dude, Suyono (International Journal of Technology and Education Research, 2025)
Sorghum (Sorghum bicolor L.) serves as an alternative food source to rice due to its rich nutritional content. The development of sorghum through breeding can be facilitated using colchicine. This study aimed to: (1) identify sorghum varieties exhibiting the best performance based on agronomic traits; (2) determine the effective colchicine treatment for increasing genetic variation in sorghum varieties; (3) identify agronomic traits with high genetic variability influenced by multiple genes; and (4) evaluate the best interaction between colchicine and variety based on sorghum agronomic traits. The study was conducted from January to April 2025 in the Greenhouse of the Agricultural Assembly and Modernization Agency, Gorontalo. The experiment employed a factorial Completely Randomized Design (CRD), where the first factor consisted of two varieties, Numbu and Kawali, and the second factor comprised four colchicine concentrations: 0 ppm, 750 ppm, 1000 ppm, and 1250 ppm. Each treatment was replicated three times, resulting in a total of 24 experimental units. The results indicated that the Numbu variety exhibited the highest genetic variability based on leaf area; a colchicine concentration of 750 ppm effectively enhanced sorghum plant variability; plant height, panicle length, and leaf area displayed high genetic variation and were controlled by multiple genes; and the interaction of the Numbu variety with 750 ppm colchicine showed the most favorable performance based on the selection traits of panicle length, plant height, and leaf area. Therefore, this combination holds potential for the colchicine-based development of sorghum